Description of Community Needs For Information on Prevention and Treatment of Dengue Hemorrhagic Fever (Dhf) at Sepauk Health Center - Eprilesko, Romantha Fieolla Crissten; Titan Ligita; Suhaimi Fauzan (Viva Medika, 2025)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by dengue virus and transmitted through the bite of female Aedes aegypti mosquitoes. The disease is endemic in tropical and some subtropical regions, becoming a serious health problem especially in developing countries, including Indonesia. DHF can trigger Extraordinary Events (KLB) and cause death. Information seeking is a community effort to gain knowledge about diseases, treatments, and health hazards, which helps them make informed health decisions. This study aimed to describe the community's need for information about the prevention and treatment of dengue hemorrhagic fever (DHF) at the Sepauk Health Center. This study was a quantitative study that used descriptive research methods. The sampling technique in this study was accidental sampling. The number of respondents was 89 people using a questionnaire research instrument for information needs related to dengue hemorrhagic fever (DHF). The results showed that the majority of respondents were aged 15-24 years (36.0%), female (64.0%), high school graduates (48.3%), housewives (33.7%), and had no history of DHF (71.9%). A total of 97.8% of respondents needed information about DHF, especially on how to prevent DHF at home. The most frequently used and desired source of information was health workers at health care facilities, while the most common barrier to obtaining information was lack of understanding of medical terms. People need information about DHF related to how to prevent DHF at home and the best approach for treatment. However, there are barriers to information due to lack of understanding of medical terms. This information is useful to support the DHF awareness campaign.